An Investigation of the Usability of Alkali-Activated Blast Furnace Slag-Additive Construction Demolition Waste as Filling Material - Sarici, Talha; Geckil, Tacettin; Ok, Bahadir; Aksoy, Huseyin Suha (Mdpi, 2025)
In this study, the usability of construction and demolition waste (CDW) aggregates as filling when stabilized with alkaline activator solution (AAS) and blast furnace slag (BFS) was investigated. The initial stage of this study involved determining the engineering properties of CDW by laboratory experiments. In the next stage, modified Proctor tests were performed to investigate the compaction behavior of CDW, to which 5% to 30% BFS was added with water or AAS. In the following stage, California bearing ratio experiments were performed to determine the mixture specimen with the highest strength. In the final stage, a weak soil layer was created in a test tank, and fillings of different thicknesses were built on it using CDW with and without additives in the determined optimum mixing ratio. Then, plate-loading tests were conducted using a model foundation to evaluate the load-deformation behavior of the fillings. The study's results indicated that adding BFS with water or AAS to CDW increased strength. Furthermore, the addition of 20% BFS yielded the highest strength value, and the CDW aggregates with the added BFS increased the ultimate bearing capacity by up to 4.72 times compared to those without the additive.
Keywords: construction and demolition wastes; geopolymer; alkaline activation; blast furnace slag; soil stabilization; plate-loading test